Exploring the factors influencing mothers' brand choices on baby diaper brands (An applied marketing research) - Pavithra, S.; Niththiya, N.; Shivany, S. (University of Jaffna, 2016)
Jaffna market is idiosyncratic, and furnish opportunities for marketers to sell their products and services to the potential customers who have returned to their habitual life. Knowing mothers' brand choice is essential for creating strategies for baby items in the market. Using Grounded Theory approach, this study explores how marketing academics and the marketers can gain fresh insights into mothers' behavior of baby diaper products in the post-conflict marketing environment. By using this methodology, researcher analyzed 40 in-depth interviews with mothers in the post conflict marketing environment. This approach allowed the development of new knowledge about the mothers' purchase behavior on diaper brands. The researcher identified unique behavioral patterns in the consumer brand choice, in a post-conflict marketing environment. The findings of the study show that mothers are seeking for a better benefit, such as hygiene, absorbency, comfortable, user-friendly, green ingredients, environmental friendly, price, softness and stretch, fashion and style, safe and secure, size and weight, which are match with their living patterns cultural norms, as well as the baby's care. Especially they more concern on brand benefits, which match the needs of the society. This research has an implication to design a unique strategy to attract the mothers to purchase particular brand in the country.
Keywords: Baby diaper brands; Grounded theory approach; Mothers brand choicepost conflict marketing environmMothers brand choicepost conflict marketing environm